2020
DOI: 10.1093/cid/ciaa1502
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19) Transmission in the United States Before Versus After Relaxation of Statewide Social Distancing Measures

Abstract: Background Weeks after issuing social distancing orders to suppress severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission and reduce growth in cases of severe coronavirus disease 2019 (COVID-19), all U.S. states and the District of Columbia partially or fully relaxed these measures. Methods We identified all statewide social distancing measures that were implemented and/or relaxed in the U.S. between March… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
2
19
1
Order By: Relevance
“…In contrast to different authors ( 1,3,4,11 ), our data showed that most social relaxing events including the opening of bars and restaurants, gyms, beauty salons, shopping centers, transportation, among others (EW 20 to 41), had a limited effect on SARS-CoV-2 cases. Although it was possible to observe an increase in cases after some of the opening events, our results indicate that such measures had a temporary and not a cumulative effect, which was also reflected in the stability of reported deaths, the most important and stable outcome, not subject to testing variations, testing policy and infrastructure ( 8 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to different authors ( 1,3,4,11 ), our data showed that most social relaxing events including the opening of bars and restaurants, gyms, beauty salons, shopping centers, transportation, among others (EW 20 to 41), had a limited effect on SARS-CoV-2 cases. Although it was possible to observe an increase in cases after some of the opening events, our results indicate that such measures had a temporary and not a cumulative effect, which was also reflected in the stability of reported deaths, the most important and stable outcome, not subject to testing variations, testing policy and infrastructure ( 8 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Several authors have assessed the impact of social relaxation events in the COVID-19 pandemic before vaccination was implemented. In general, the proposed analyzes are based on projections by epidemiological models ( 1,2 ), shorter follow-up periods ( 3 ), or using data from government databases ( 4 ). Such information is crucial, providing projections on the pandemic in different scenarios.…”
mentioning
confidence: 99%
“…Our findings are consistent with previous ecological studies investigating the effect of social distancing on risk of COVID-19 [21][22][23][24][25][26][27][28] . In one recent study that also used estimates of social distancing based on Unacast data, each one-unit increase in social distancing was associated with a 29% reduced risk of COVID-19 incidence and a 35% reduced risk of COVID-19 mortality 22 at the county-level.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, lifting NPI abruptly diminishes the gains accumulated by previously implemented policies 7,13 . In our study, individuals who relaxed social distancing measures 14 or had contact with COVID-19 individuals without mask 15,16 had the highest risk of acquiring SARS-CoV-2 infection.…”
mentioning
confidence: 57%